Expressividade em Jornalismo: interfaces entre Comunicação, Fonoaudiologia e Educação - Penteado, Regina Zanella; Pechula, Marcia Reami (Sociedade Brasileira de Estudos Interdisciplinares da Comunicação (INTERCOM), 2018)
Abstract This paper approaches expressiveness in the education of journalists in the interfaces of Communication, Speech-Language Pathology and Audiology and Education. Its purpose is to highlight expressiveness in Journalism as a dimension of education and of training in Communication in contemporary times. The methodological approach involves discussing expressiveness in three instances: in the history of Speech-Language Pathology and Audiology practices with journalists; in the characterization of actions in the educational processes of journalists; and in questioning the conceptions and practices regarding its contributions when education is concerned. The study subsidizes a broader understanding of expressiveness in Journalism training: one that is interactive, dialogic and creative, able to deactivate standardization and spectacularization, as well as promoting processes of singularity, subjectivation and professionalization.

Resumen El artículo aborda la expresividad en la formación del periodista en las interfaces Comunicación, Fonoaudiología y Educación. Tiene por objetivo dar visibilidad a la expresividad en Periodismo como dimensión de la educación y de la formación en Comunicación en la contemporaneidad. El recorrido metodológico involucra tematizar la expresividad en tres instancias: en la historicidad de la práctica fonoaudiológica con periodistas; en la caracterización de las acciones en procesos educativos en la formación de periodistas; y en la problematización de las concepciones y prácticas, con cuestionamiento de las contribuciones en lo que concierne a la educación. El estudio subsidia una comprensión ampliada de la expresividad en la formación en Periodismo: que se pueda decir interactiva, dialógica y creativa, con capacidades de deshabilitar dispositivos de homogeneización y de espectacularización, además de agenciar procesos de singularización, de subjetivación y de profesionalización.

Resumo O artigo aborda a expressividade na formação do jornalista nas interfaces Comunicação, Fonoaudiologia e Educação. Tem por objetivo dar visibilidade à expressividade em Jornalismo como dimensão da educação e da formação em Comunicação na contemporaneidade. O percurso metodológico envolve tematizar a expressividade em três instâncias: na historicidade da prática fonoaudiológica com jornalistas; na caracterização das ações em processos educacionais na formação de jornalistas; e na problematização das concepções e práticas, com questionamento das contribuições no que concerne à educação. O estudo subsidia uma compreensão ampliada da expressividade na formação em Jornalismo: que se possa dizer interativa, dialógica e criativa, com capacidades de desabilitar dispositivos de homogeneização e de espetacularização, além de agenciar processos de singularização, de subjetivação e de profissionalização.
Expressiveness in Journalism: interfaces between Communication, Speech-Language Pathology and Audiology and Education
Expresividad en Periodismo: interfaces entre Comunicación, Fonoaudiología y Educación
Keywords: Communication; Education; Expressiveness; Journalism; Speech-Language Pathology and Audiology; Comunicação; Educação; Expressividade; Jornalismo; Fonoaudiologia